Job-hopping amongst African Black senior management in South Africa - Khanyile C.C. Nzukuma (SA Journal of Human Resource Management, 2011)
Orientation: The study focuses on understanding labour turnover trends amongst African Black senior managers in South Africa. There is a perception that turnover amongst African Black senior managers is higher than average. There is also a perception that African Black senior managers are only motivated by financial rewards when considering job change. Research purpose: The study focused on understanding why African Black senior managers have a propensity to change jobs and how organisations can resolve the trend.